RETRIAL QUEUEING SYSTEMS WITH FINITE NUMBER OF TRAFFIC SOURCES - Коба, О. В. (Science-based technologies, 2016)
Retrial (return call) queuing systems theory have rapidly developed since the 1980s. The classical queuing theory consider queues without call blocking; thus, given an idle channel, a call being in the system is forwarded to this channel immediately. Such models are obviously an idealized pattern of real processes. An important type of blocking systems is retrial (return call) systems. Retrial queues are various and widely used. However, virtually all systems studied are considered to have exponentially distributed time in the orbit, which often does not correspond to actual systems (air field, computer, telefone systems). In article closed queueing systems with deterministic retrial time and finite number of traffic sources on non-Markov type and were investigated. Embedded Markov chains and the system of steady-state equations were built. Systems solutions methods were derived. System functioning characteristics, such as efficiency of service channel, mean waiting time of request, mean number returns of request and so on, were determined.